Changing the Africa's impoverishing economic model: Towards a rewarding sustainable specialization model with a new factor of production - (:unkn) unknown (My University, 2017)
This paper highlights the impoverishing character of Africa’s economic model in its world merchandise trade. With a view to reduce the ousting of the wealth of the continent by its trading partners, we develop a neo-factorial specialization model in which we introduce technology and raw materials as endogenous factors of production of manufactured goods. In addition, we distinguish between skilled labor and unskilled. Considering raw commodities as a factor production (natural capital) and making technology and skilled labor factors endogenous allows us to understand why Africa is historically specialized in raw material exports. We show how Africa can, thanks to its advantage in natural resources, accumulate technology and human capital necessary to its industrialization in the second phase of the model, allowing it to eliminate the impoverishing effects of trade. The model predictions are quite optimistic in the second phase of Africa's opening process to the world. Calibrating the model on real data, results are consistent with some goals of sustainable development particularly in its economic and social dimensions. The environmental dimension is however difficult to reconcile with both others.
Keywords: African Research